Consistency analysis of the Sysmex UF‐5000 and Atellica UAS 800 urine sedimentation analyzers. Issue 9 (16th August 2022) - Liu, Hai; Li, Qing; Zhang, Yiduo; Huang, Dongyue; Yu, Fan
Abstract: Objective: To evaluate the consistency between the results of Sysmex UF‐5000 system and Atellica® UAS 800 Urine Sediment Analyzer. Methods: A total of 636 random urine samples were collected from inpatients and outpatients from March to September 2021. Urine was collected for analysis by the Sysmex UF‐5000, Atellica UAS 800 systems, and manual microscopic examination. The results of manual microscopy as the gold standard, the coincidence rate and false‐negative rate of Sysmex UF‐5000 and Atellica UAS 800 systems in the detection of red blood cells, white blood cells, and casts were calculated. Results: The coincidence rates of red blood cells, white blood cells, and cast, crystals, and other sediment components for the Sysmex UF‐5000 system were 85.37%, 87.89%, 91.67%, 88.36%, and 71.86%. The false‐negative rates were 28.47%, 3.75%, 68.97%, 37.25%, and 30.63%. The coincidence rates of red blood cells, white blood cells, and cast, crystals, and other sediment components for the Atellica UAS 800 system were 85.06%, 90.25%, 59.12%, 91.67%, and 67.45% and the false‐negative rates were 60.42%, 21.25%, 36.21%, 19.64%, and 35.80%. Conclusion: Two instruments are superior in the detection of red blood cells and white blood cells. The Atellica UAS 800 system with image review has a good coincidence rate in the identification of crystals and casts. The identification of various sediment components in urine by both instruments meets the laboratory requirements. Two instruments with different methodologies have their own characteristics, and we should reasonably use them according to the conditions of the laboratory. Abstract : Types of sediment detected by the Sysmex UF‐5000 and Atellica UAS 800 system. Sysmex UF‐5000 and Atellica UAS 800 with different methodologies have their own characteristics. The Atellica UAS 800 system with image review has a good coincidence rate in the identification of crystals and casts. The identification of various sediment components in urine by both instruments meets the laboratory requirements